A GUIDE TO CHRISTIAN SPIRITUAL FORMATION: HOW SCRIPTURE, SPIRIT, COMMUNITY, AND MISSION SHAPE OUR SOULS. BY EVAN B. HOWARD. - Novel Priyatna (Universitas Pelita Harapan, 2020)
Although interest in Christian spiritual formation among evangelicals, especially in Western society, has been at a critical stage, Howard stresses the importance of Christian spiritual formation. Christian spiritual formation helps individuals and Christian communities grow deeper in their relationship with the Triune God because in it the Holy Spirit, Scripture, community, and mission are interconnected with one another. Furthermore, without Christian spiritual formation, Christian institutions find it difficult to perform their roles well. Therefore, this book challenges Christian leaders such as educators, pastors, spiritual directors, and other church leaders to become God’s instruments in transforming believers to have Christlike character in their lives.BAHASA INDONESIA ABSTRAK: Meskipun minat dalam formasi rohani Kristen di kalangan kaum Injili, khususnya di masyarakat Barat, telah berada pada tahap kritis, Howard menegaskan pentingnya formasi rohani Kristen. Formasi rohani Kristen membantu individu-individu dan komunitas-komunitas Kristen untuk bertumbuh lebih dalam terkait hubungan mereka dengan Allah Tritunggal karena didalamnya Roh Kudus, Alkitab, komunitas, dan misi saling berhubungan satu sama lain. Lebih jauh lagi, tanpa formasi rohani Kristen, lembaga-lembaga Kristen sulit melakukan perannya dengan baik. Oleh karena itu, buku ini menantang para pemimpin Kristen seperti pendidik, pendeta, direktur spiritual, dan pemimpin-pemimpin gereja lainnya untuk menjadi alat Tuhan dalam mengubah orang-orang Kristen agar dapat memiliki karakter seperti Kristus dalam kehidupan mereka.